Золотое притяжение - Леонов Николай Иванович (Русский бестселлер, 2018)
Экземпляры: аб. ЦБ (20180917) / Инвентарный номер: 4889 / Цена: / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Л 47 / ГРНТИ: 17 / ББК: 84(2Рос=Рус)6